2008
DOI: 10.1159/000112607
|View full text |Cite
|
Sign up to set email alerts
|

Tadalafil and Fluoxetine in Premature Ejaculation: Prospective, Randomized, Double-Blind, Placebo-Controlled Study

Abstract: Introduction: Premature ejaculation (PE) is a common male sexual disorder. An ideal, reliable and effective treatment is desired by many men and couples affected by this condition. Aim: Evaluate if the association of a phosphodiesterase-5 inhibitor, tadalafil, and a selective serotonin reuptake inhibitor, fluoxetine, can prolong the intravaginal ejaculatory latency time (IELT) in men with lifelong premature ejaculation. Methods: Sixty patients with lifelong premature ejaculation and without erectile dysfunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
123
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(125 citation statements)
references
References 33 publications
1
123
0
1
Order By: Relevance
“…A total of 41 RCTs that evaluated an SSRI against a comparator (placebo, no therapy, another SSRI, or another agent) were identified and were included in both the rapid review for the HTA short report and the full systematic review. Twenty-five of these RCTs (Atmaca et al 2002;Atmaca et al 2003;Biri et al 1998;Buvat et al 2009;Kara et al 1996;Kaufman et al 2009;Manasia et al 2003;Mattos et al 2008;McMahon 1998;McMahon et al 2010;Mendels et al 1995;Murat Basar et al 1999;Panshou and Xie 2004;Pryor et al 2006;Safarinejad and Hosseini 2006;Safarinejad 2008;Safarinejad 2006;Waldinger et al 1994;Waldinger et al 1997;Waldinger et al 1998;Waldinger et al 2001a;Waldinger et al 2001b;Waldinger et al 2003;Yilmaz et al 1999;Zhou 2007) had been previously included by eleven systematic reviews ( Data from these 25 RCTs were extracted from the systematic reviews they were reported in for the rapid review, and directly from the RCT publication obtained in full for the full systematic review.…”
Section: Search Resultsmentioning
confidence: 99%
“…A total of 41 RCTs that evaluated an SSRI against a comparator (placebo, no therapy, another SSRI, or another agent) were identified and were included in both the rapid review for the HTA short report and the full systematic review. Twenty-five of these RCTs (Atmaca et al 2002;Atmaca et al 2003;Biri et al 1998;Buvat et al 2009;Kara et al 1996;Kaufman et al 2009;Manasia et al 2003;Mattos et al 2008;McMahon 1998;McMahon et al 2010;Mendels et al 1995;Murat Basar et al 1999;Panshou and Xie 2004;Pryor et al 2006;Safarinejad and Hosseini 2006;Safarinejad 2008;Safarinejad 2006;Waldinger et al 1994;Waldinger et al 1997;Waldinger et al 1998;Waldinger et al 2001a;Waldinger et al 2001b;Waldinger et al 2003;Yilmaz et al 1999;Zhou 2007) had been previously included by eleven systematic reviews ( Data from these 25 RCTs were extracted from the systematic reviews they were reported in for the rapid review, and directly from the RCT publication obtained in full for the full systematic review.…”
Section: Search Resultsmentioning
confidence: 99%
“…Another study was designed to investigate the efficacy of tadalafil 20 mg on IELT in men with LL-PE, taken before intercourse in association with SSRI taken once a week (fluoxetine 90 mg) or alone. 46 The authors found that the increase in IELT was greater in patients who used fluoxetine 90 mg taken once a week and tadalafil 20 mg before sexual relations, when compared with placebo, fluoxetine or tadalafil alone. However, this study had no crossover of the groups that would probably allow better understanding of whether such results remained consistent.…”
Section: Pde5-i In Pementioning
confidence: 98%
“…39,41,141,166 A further 16 RCTs additional to those already included reviews were identified for inclusion, [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107] resulting in a total of 42 RCTs that evaluated SSRIs. Fourteen of the 16 additional RCTs identified by the literature search were considered to be at overall unclear risk of bias.…”
Section: Assessment Of Clinical Effectivenessmentioning
confidence: 99%